Accurate fault location of two-terminal transmission line based on one end voltage measurement and Smooth Support Vector Machines - Alanzi E.A.J.; Younis M.A.A. (2023)
This paper presents a new technique for accurate fault location based on voltage measurement from one end of the two-terminal transmission line and Smooth Support Vector Machine (SSVM). Due to common problems of current transformer during fault location and as a result increasing the cost and reduction of the accuracy, proposed technique is independent of current measurement and based on one terminal voltage measurement of the transmission line. Post-fault voltage at one end of the line is measured and used in calculation of the fault location. GPS (global positioning system) is not required for this technique resulting in a reduction of economic cost. Using the proposed technique, fault location can be estimated with a lower than 0.025% error without using current transformers and GPS. EMTP/ATP simulation and SSVM results show that the proposed fault location technique is independent of fault type, fault resistance and fault inception of the transmission line. 2011 IEEE.